Developing psychomotor evaluation instrument of biochemistry practicum for university students of biology education - Etika Dyah Puspitasari; Mohamad Joko Susilo; Novi Febrianti (REID (Research and Evaluation in Education), 2019)
Practicum is one of the important aspects of the learning of biology. There is no psychomotor evaluation instrument that is valid and reliable. This study is aimed at developing a valid and reliable psychomotor evaluation instrument for biochemistry practicum. The study is developmental research using the 4-D model of ‘define, design, develop, and disseminate’. Instrument validation was carried out through construct validation. The findings show that the developed instrument is characterized by a high level of construct validity although the reliability measure is not very well-estimated. The instrument is constructed of four factors of perception, set, guided response, and mechanism developed into 80 statement items.